Effect of current, time, ethanol concentration, and pH electrolyte on ZnO coated carbon fiber using electrochemical deposition method - Salahuddin Junus; Gindeka Bimara Aryantaka; Rizky Akhmad Prayogi; Mochamad Asrofi; Rahma Rei Sakura; R. Puranggo Ganjar Widityo; Robertus Sidartawan (Universitas Muhammadiyah Magelang, 2023)
One of the recent developments in carbon fiber is using nano zinc oxide (ZnO) as a coating on carbon fiber to create piezoelectric materials. Piezoelectric materials can generate electricity when subjected to mechanical pressure or strain, and vice versa. ZnO nanomaterials have been a focal point of research due to their high surface-to-volume ratio and high reactivity. This study reported on the use of ZnO for coating agents in carbon fiber sensors. The novelty in this research is the composition of current, time, ethanol concentration, and pH electrolyte to produce the optimum composition of piezoelectric material. The process was conducted using an electrochemical method, which converts electrical energy into chemical energy through electro-deposition. This study considers four independent variables: electrolyte current (1.2 A and 1.4 A), electrolyte pH (2.0, 4.0, and 6.0), ethanol concentration (70% and 96%), and coating duration (90, 180, and 270 seconds). The results show that 1.4 A produces the highest average voltage, followed by electrolyte pH 6 and 70% ethanol concentration. The best coating time was 270 seconds producing the highest average voltage. Micro and SEM confirm that 1.4 A produced a thicker and more uniform layer compared to 1.2 A. High pH, 70% ethanol concentration, and longer coating time also contributed to the formation of thicker layers. XRD test shows that the layers formed had amorphous and hexagonal crystal structures. The average crystal diameter size varies depending on the combination of independent variables used in the coating process. With these results, piezoelectric has potential as a pulse sensor material.